2021
DOI: 10.2147/ijgm.s310414
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Masked Hypertension Measured by Ambulatory Blood Pressure Monitoring and Left Ventricular Global Longitudinal Strain: A Retrospective Study

Abstract: Masked hypertension (MHT), as an independent clinical entity, the cardiac dysfunction caused by it can be early detected through left ventricular global longitudinal strain (GLS), yet the quantitative relation between MHT and GLS is still unclear. Therefore, we tried to conduct a community-based retrospective study to define this relationship. Patients and Methods: A total of 308 enrolled participants from Dongguan, China, were divided into non-hypertension (NHT) and MHT groups. Baseline characteristics were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…There was statistically significant difference between two studied groups regarding GLS: (p value 0.001). This came in accordance with Fu et al [16] who showed that GLS was lower ('worse') in the prehypertensive group being compared with the normotensive group (202).…”
Section: Discussionsupporting
confidence: 91%
“…There was statistically significant difference between two studied groups regarding GLS: (p value 0.001). This came in accordance with Fu et al [16] who showed that GLS was lower ('worse') in the prehypertensive group being compared with the normotensive group (202).…”
Section: Discussionsupporting
confidence: 91%
“…Demographic and clinical characteristics of normotensive (reported in Table 2, Supplemental Digital Content, http://links.lww.com/HJH/C114) and MH participants were similar in four out of six studies. In the remaining two reports, individuals with MH were more likely to be overweight/obese [21,22] and older [22] than their normotensive counterparts.…”
Section: Resultsmentioning
confidence: 97%
“…GLS); the remaining 20 ones were review, commentary, editorial articles and case report. Thus, a total of six studies including participants with MH and containing sufficient clinical and cardiac imaging data (namely GLS), were included in the final review [18][19][20][21][22][23] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations